ICT skills and challenges faced by high school teachers of Inle Lake located in the Nyaungshwe township of Shan State in Myanmar - May Theint Thu (Journal of Green Learning, 2022)
In western Shan State of Myanmar, there is a picturesque lake, famous for its floating villages and gardens and the unique way of life of the local Intha people, with their living communities based entirely on the water. The present survey research was aimed at identifying the ICT facilities, skills, usage, and the problems faced by the high school teachers of basic education while using ICT. The population of the study comprised the teachers of 17 Inle villages. Instrument was developed by the first author. About 102 state high school teachers were selected from three government high schools. Descriptive statistics were used to analyze the data. The findings revealed that only some of the teachers have computers and Internet facilities at home and school. They are expert at simple skills like searching and browsing internet, social networking,  and MS word but are less skilled or poor on other skills like using MS access,  discussion forums/blogs and Windows file management. Teachers spend more time on computers for academic and other purposes than for recreational purpose. They believe that the use of ICT supports their learning, lack of technical support at home and at school, load shedding at home and at school and signal problem in Internet at home and are the problems faced by most of the teachers. Thus, the government high schools should invest more on improving the infrastructure to address the ICT related problems of teachers at the schools.